ALBUMIN AND HEMOGLOBIN VALUE IN CHRONIC RENAL FAILURE (CRF) PATIENTS WITH DIABETES AND NON-DIABETES - Diyah Candra Anita (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Malnutrition is a common problem in patients with chronic renal failure (CRF) with Diabetes Mellitus and Non-Diabetes Mellitus. Assessments of nutritional status in CRF patients are required to measure some important parameters including serum albumin and hemoglobin. This study aimed to fi gure out the differences of nutritional status between CRF patients with diabetes mellitus and without diabetes mellitus in the inpatient unit of PKU Muhammadiyah Hospital Yogyakarta, by examining the levels of albumin and hemoglobin serum. Methods. This study applied cross sectional method of which measuring instruments were patients’ medical records of laboratory tests. This research used accidental sampling method involving 30 patients as samples. Result. The results of independent t-test showed that there was no signifi cant differences between the levels of albumin (p = 0.917) and hemoglobin (p = 0.168) between the group of non DM CRF patients and CRF patients with M. Discussion. Therefore, further research should be performed by using a larger sample size as well as considering patients’ historical background of hemodialysis treatment.Keywords: Diabetes Mellitus (DM), Chronic Renal Failure (CRF), albumin, hemoglobin